PENGARUH PENGETAHUAN PERPAJAKAN, PENERAPAN SISTEM E-FILING DAN KUALITAS PELAYANAN TERHADAP KEPATUHAN WAJIB PAJAK - Hilman, Muhammad (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2022)
This research aimed to examine and analyze the effect of implementation of efiling ans service quality on the individual taxpayers’ compliance at the Pratama Gresik Selatan Tax Office. While, the research was quantitative with questionaires as the instrument. Moreover, the data collection technique used purposive sampling, in which the sample was based criteria given. In line with, there were 100 individual taxpayers registered at the Pratama Gresik Selatan Tax Office as sample. Furthermore, the data analysis technique used multiple linear regression with SPSS. The results of this study indicate that the variable of taxation knowledge and the implementation of the E-Filing System has a positive effect on individual taxpayer compliance, it will also affect the compliance of individual tax payers getting better and increasing. While the quality of service does not have a positive effect on individual taxpayer compliance.